Rethinking Trust: The Role Of Social Support, Presence, And Content Quality In Shaping Social Commerce Intentions - Sofa Fikri Haikal Haikal; Rini Kuswati (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to examine the impact of social support, social presence, and quality of the information regarding the plan to use social commerce, with trust serving as a variable of mediation. The study adopts a quantitative approach involving 151 respondents residing in Surakarta who have experience purchasing via social commerce platforms. Data were collected through structured questionnaires and analyzed using Structural Equation using the Partial Least Squares (PLS) approach for modeling (SEM). The results show that social support significantly affects both trust and intention to use social commerce. Social presence and content quality significantly influence want to engage in social trade, but not trust. Furthermore, trust itself does not significantly influence people's intentions to utilize social commerce and does not mediate the influence of the independent variables. These results highlight that while interactional and content-based factors directly influence user behavior, trust may not always serve as a central psychological mechanism in digital purchasing decisions.